Promoting four-electron oxygen reduction reaction with chiral semimetals PtGa - Sun, Shu-Bin; Ma, Dan-Dan; Ma, Jin-Fu; Lei, Lei; Wang, De-Gao; Zhan, Jie; Sun, Yan; Wang, Lei; Li, Guo-Hua; Yan, Jian-Hua; Felser, Claudia; Li, Guo-Wei; et al. (Rare metals, 2025)
Spin polarization has emerged as a promising strategy for designing high-performance catalysts, particularly for reactions involving intermediates with triplet-singlet transitions, such as the oxygen reduction reaction (ORR). However, the creation of spin polarization typically requires complex phase structures or external fields, making it challenging to understand the mechanisms of spin manipulation and to search for high-performance catalysts. Chiral crystals, such as B20 compounds, inherently exhibit spin polarization when subjected to an electric current due to the coupling of crystal structure chirality and electronic chirality, offering an excellent platform for modulating the ORR process. In this study, nanosized PtGa alloys were successfully dispersed onto carbon and exhibited a distinct circular dichroism signal, indicating the presence of electron spin polarization. As an ORR catalyst, this chiral alloy demonstrated a high half-wave potential of 0.91 V, a mass activity of 1.17 A mgPt−1, and a specific activity of 4.08 mA cm−2, surpassing the performance of state-of-the-art Pt/C catalysts in both activity and cost. Notably, the alloy facilitates a direct four-electron transfer pathway, significantly reducing the formation of H2O2 as a side product to an impressively low yield of 0.5%. This work provides an effective approach for generating spin-polarized electrons, thereby advancing the development of cutting-edge ORR catalysts.